The use of gnotobiological models for the studies of immune mechanisms - Sterzl, J; Mandel, L; Stĕpánková, R (Die Nahrung, 1987)
Germfree (GF) animals are widely used for discrimination of natural mechanisms (genetically determined) from adaptive mechanisms of immunity induced by external antigens. GF rats fed at least for first 5 days after birth with artificial diet LNa, deficient in unsaturated fatty acids, were in contrast to those fed with K 50 diet deeply suppressed in humoral and cellular immune reactivities during their life. GF piglets, deprived from maternal colostrum (CF) as a source of passively transferred maternal antibody, immunized with preformed Ag/Ab complexes (HSA anti HSA) responded according to the composition of complexes (Ab excess, equivalence, Ag excess) by low or high dose tolerance or by secondary response. Similar pictures of response were obtained in groups of presensitized GF-CF piglets by immunization with different doses of antigen. It is concluded that 3 different types of response are the result of Ag/Ab complexes acting or formed on the lymphocyte membrane and exerting stimulatory or down-regulatory signals.
Keywords: Animals; gnotobiologické modely; Research Design; inbrední kmeny potkanů; Immune Tolerance; prasata; Immunization, Passive; Immunity; Rats, Inbred Strains; imunita; dieta; Germ-Free Life; Diet; kalorimetrie; fyziologie výživy zvířat; Swine; pasivní imunizace; Animal Nutritional Physiological Phenomena; Calorimetry; krysa rodu Rattus; imunologická tolerance; zvířata; výzkumný projekt; Rats